Paranticoma lepta sp. n. and Elzalia bipectinella Hope & Aryuthaka, 2009 from water bodies of Vietnam - Long, Phan Ke; Tu, Nguyen Dinh; Gagarin, Vladimir G. (Zootaxa, 2019)
Two nematode species found in water bodies of Vietnam are described and illustrated. Paranticoma lepta sp. n., found in mangroves of the Yen River estuary is morphologically close to P. bendaense Micoletzky, 1930 and P. tricerviseta Zhang, 2005. From the former species it differs by the shorter cephalic setae and shorter tail, more anteriorly located cervical setae and shorter spicules. From the second species it differs by its thicker body, comparatively longer tail, longer spicules and absence of tooth-like structures in stoma. An illustrated description of males and females of Elzalia bipectinella Hope & Aryuthaka 2009 is given, originally described from mangrove forest in the Andaman Sea coastal zone of east Thailand. Females of this species are described for the first time.